Appearance of levator ani muscle subdivision defects on level III vaginal support structures in women with and without pelvic organ prolapse: an MRI study - Horcicka, L; Krcmar, M; Nemec, M; Hympanova, L; Feyereisl, J; Krofta, L (International urogynecology journal, 2023)
INTRODUCTION AND HYPOTHESIS: Injury of the levator ani muscle (LAM) is a significant risk factor for pelvic organ prolapse (POP). The puborectalis (PRM) and pubovisceral (PVM) subdivisions are level III vaginal support structures. The null hypothesis was that there is no significant difference in patterns of LAM subdivisions in healthy nulliparous women. Secondarily, we evaluated the presence of different LAM injury in a POP-symptomatic cohort. METHODS: This retrospective magnetic resonance imaging study included: 64 nulligravidae without any pelvic floor dysfunction (PFD) and 526 women of various parity with symptomatic POP. Primary outcome was PVM and PRM morphology on the axial planes: the attachment site on the pubic bone, and the visible separation/border between the PVM and PRM. The attachment was scored as "normal" or "abnormal". The "abnormal" attachment was divided in two types: "type I"-loss of the muscle substance, but preservation of the overall muscle architecture-and "type II"-muscle detachment from the pubic bone. RESULTS: The puboanal muscle (PAM) subdivision was evaluated as a representative part of the PVM. The PAM and PRM attachments and separation were distinguished in all asymptomatic nulliparae. PAM and PRM attachments did not significantly differ. POP group characteristics were parity 1.9 ± 0.8, instrumental delivery 5.6%, hysterectomy or POP surgery 60%, all Pelvic Organ Prolapse Quantification (POP-Q) stages, LAM defect 77.6% (PRM: 77.1%; PAM: 51.3%). Type I injuries were more frequent (PRM 54.7%; PAM 53.9%) compared with type II (PRM 29.4%; PAM 42.1%). CONCLUSIONS: A LAM defect was present in 77.6% of women with symptomatic POP. In PRM and PAM subdivisions type I injury was more frequent than type II.
Keywords: Magnetic Resonance Imaging; Pelvic Floor; Vagina; Pelvic Organ Prolapse; lidé; retrospektivní studie; prolaps pánevních orgánů; Female; Pregnancy; těhotenství; magnetická rezonanční tomografie; Retrospective Studies; pánevní dno; vagina; ženské pohlaví; Humans